Avaliaç\~ao da qualidade nutricional de cultivares de milho no Huambo - Maria Pepeka (European Regional Science Association (ERSA), 2011)
This paper presents a summary on the evaluation of food quality of corn cultivars used in Huambo. Planted in large scale in the whole area of the Province, is usually processed into flour (osema). Corn is stepped to take the tegumneto and then placed in a pot next to the hot ash for two days or more, which causes a slight fermentation, then it will set foot on the stone (ohanda) or pestle (otchine) of who gets the corn flour (osema). The chemical analysis of four cultivars most widespread in Huambo and two regional (Round and White Horse Tooth) and two introduced SAM3 ZM521 demonstrate and the protein, fat, fiber and ash four cultivars distinguished from each other. This time the corn is reflected in a foodstuff of great importance for the promotion of local varieties is an essential element in fighting hunger and contributes to food security and hence to regional development
Keywords: 330; cultivars; corn; flour; food security